A regioselective and convenient one-pot multicomponent synthesis of polyfunctionalized 4-aryl-2-cyanoimino-3, 4-dihydro-1H-pyrido[2, 3-d]pyrimidines. Issue 18 (17th September 2019) - Hussein, Bahgat R. M.; Moustafa, Amr H.
Abstract: A novel series of 5, 7-diamino-4-aryl-6-cyano-2-cyanoimino-3, 4-dihydro-1 H -pyrido[2, 3- d ]pyrimidines (aryl-CIDHPPMs) 3a–i was prepared via the one-pot four-component reaction of cyanoguanidine with aromatic aldehydes and malononitrile with molar ratio (1:1:2) using sodium methoxide as catalyst. These new polyfunctionlized aryl-CIDHPPMs were also synthesized by a classical route via reaction of cyanoguanidine with the respective arylidenes of malononitrile dimer under the same condition. In the same manner, the reaction of cyanoguanidine with isatinylidene of malononitrile dimer afforded the new spiro -pyrido[2, 3- d ]pyrimidines 7 . While using aromatic aldehydes having electron donating groups (hydroxyl or dimethylamino groups) gave 4-Amino-2-aryl-6-methoxypyridine-3, 5-dicarbonitrile 5a, b . GRAPHICAL ABSTRACT: